PERSEPSI MASYARAKAT TERHADAP PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT PLN SEKTOR PEMBANGKITAN TARAHAN PROVINSI LAMPUNG - Dedeh Kurniasih Kusnani; Sumaryo Gitosaputro; Indah Nurmayasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
Indicators of Corporate Social Responsibility programs by PT PLN Tarahan Power Sector, South Lampung are suitability, sustainability, and sociality of CSR programs. CSR programs are given for community and the environment. People who receive the programs will have perceptions. The external and internal factors of individuals suspected related to the perceptions are people’s age, gender, educational level, emotional level, income level, the number of family members, and benefits of CSR programs. The purposes of this research are to determine the level of implementation of CSR programs, the level of community’s perceptions on CSR programs, and the factors related to community’s perceptions. This research uses a survey method. The number of samples in this research are 84 households in “Dusun” Mataram, Sukamaju, Gotong Royong, and Kampung Baru. The results showed that the implementation of CSR programs by PT PLN has not been successful because not all people were involved in the programs, and the programs were not suitable to community’s needs. The level of community’s perceptions on CSR programs was not good and the factors significantly correlated to community’s perceptions were people’s age, educational level, emotional level, and benefits of CSR programs. Keywords: perception, corporate social responsibility (CSR), community